Environmental life-cycle analysis of hydrogen technology pathways in the United States - Elgowainy, Amgad; Vyawahare, Pradeep; Ng, Clarence; Frank, Edward D.; Bafana, Adarsh; Burnham, Andrew; Sun, Pingping; Cai, Hao; Lee, Uisung; Reddi, Krishna; Wang, Michael (Frontiers in Energy Research, 2024)
Hydrogen is a zero-carbon energy carrier with potential to decarbonize industrial and transportation sectors, but its life-cycle greenhouse gas (GHG) emissions depend on its energy supply chain and carbon management measures (e.g., carbon capture and storage). Global support for clean hydrogen production and use has recently intensified. In the United States, Congress passed several laws that incentivize the production and use of renewable and lowcarbon hydrogen, such as the Bipartisan Infrastructure Law (BIL) in 2021 and the Inflation Reduction Act (IRA) in 2022, which provides tax credits of up to 3/kg depending on the carbon intensity of the produced hydrogen.A comprehensive life-cycle accounting of GHG emissions associated with hydrogen production is needed to determine the carbon intensity of hydrogen throughout its value chain. In the United States, Argonne's R&D GREET® (Greenhouse Gases, Regulated emissions, and Energy use in Technologies) model has been widely used for hydrogen carbon intensity calculations. This paper describes the major hydrogen technology pathways considered in the United States and provides data sources and carbon intensity results for each of the hydrogen production and delivery pathways using consistent system boundaries and most recent technology performance and supply chain data.